0799 Feasibility Of Recording Sleep Quality And Sleep Duration Using Fitbit In Children With Asthma. (27th April 2018) - Sheth, A; Yip, H; Jaimini, U; Sridharan, V; Venkataramanan, R; Thirunarayam, K; Banerjee, T; Kalra, M
Abstract: Introduction: Sleep disorders are common in children with asthma and have been implicated in poor asthma control. Smart wearables such as the Fitbit wristband allow monitoring patients sleep duration and quality in their natural surroundings. However, the utility and efficacy of using wearable devices to monitor sleep quality and sleep duration in pediatric patients with asthma has not been established. Methods: Children, ages 5 yrs. to 18 yrs., participating in kHealth Asthma research study at Dayton Children's Hospital were included. The kHealth kit includes an android tablet with a mobile health application that asks contextually relevant questions as well as collects personalized data from bluetooth connected Fitbit Charge 2, Peak flow meter, and Foobot, an indoor air quality monitor. Fitbit software calculated time in bed, sleep time and time in REM sleep, light sleep and deep sleep was downloaded on all subjects. Sleep efficiency was calculated as sleep time/time in bed and proportion of time in each sleep stage was calculated. Results: Preliminary data from 14 children was analyzed. The average time in bed was 534 ± 77 minutes and average sleep time was 476 ± 70 minutes. The average time in REM sleep was 88 ± 25 minutes and average time in light sleep was 287 ± 37 minutes and in deep sleep was 92.5 ± 27.8 minutes. Sleep efficiency was 89%. Proportion of sleep time spent in REM sleep was 20 % and in light sleep was 60.5% and in deep sleep was 18.5 %. These correlate well with polysomnographic based normative data in children. Conclusion: Our findings support the potential of using wrist-worn devices to continuously monitor sleep duration and quality in children with asthma. Future work seeks to evaluate the effect of sleep on asthma outcomes in children. Support (If Any): Research was supported by NICHD of the National Institutes of Health under award number 1R01HD08713201 (PI: Amit Sheth). The content is solely the responsibility of the authors and does not necessarily represent the official views of the National Institutes of Health.